2014
DOI: 10.1007/978-3-319-06773-5_40
|View full text |Cite
|
Sign up to set email alerts
|

Model Driven Testing for Cloud Computing

Abstract: In this paper, the authors present a proposal to support the creation of test cases for software systems under cloud computing environments. This approach is based on Model Driven Engineering (MDE). A Methodology and metamodels are proposed to support the generation of test cases. Specific metamodels for cloud computing environments are provided. Business models are created conform to UML (including profiles) and test cases are created conform to a metamodel that is independent testing platform. Both models ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In contrast, although (TUNG; LIN; SHAN, 2014) was considered complete according to the number of pages and proposes a framework for TaaS security testing, it did not achieve the minimum score required. Finally, although the paper of Oliveira et al (OLIVEIRA et al, 2015) showed a five-page limitation, it achieved a significant score of 2.7 points and covered most of the issues and quality criteria. The final quality assessment of all selected primary studies is available 15 Has the approach adopted been evaluated or validated by the authors?…”
Section: A2422 Quality Assessmentmentioning
confidence: 99%
“…In contrast, although (TUNG; LIN; SHAN, 2014) was considered complete according to the number of pages and proposes a framework for TaaS security testing, it did not achieve the minimum score required. Finally, although the paper of Oliveira et al (OLIVEIRA et al, 2015) showed a five-page limitation, it achieved a significant score of 2.7 points and covered most of the issues and quality criteria. The final quality assessment of all selected primary studies is available 15 Has the approach adopted been evaluated or validated by the authors?…”
Section: A2422 Quality Assessmentmentioning
confidence: 99%